Oxalate Induced Correction of the Plasma Antithromboplastin Deficiency in the Aging Arteriosclerotic Subject - Commers, L. R; Pilgeram, L. O (Thrombosis and Haemostasis, 1963)
Intravenous heparin will correct the enhanced thromboplastin generation of oxalated plasma obtained from the human arteriosclerotic patient. It will not,however, correct the deficiency of antithromboplastin activity in non-oxalated plasma obtained from the pathological subject. This deficiency of antithromboplastin disappears if oxalate ion is introduced into the heparinized plasma.